Bridging the data divide: challenges and opportunities for trauma registries in conflict-affected MENA countries: a qualitative analysis of key informant interviews - Tracy Daou; Fatima Mansour; Zahi Abdul Sater; Hady Naal; Lubna Jaber; Anika Gnaedinger; Ghassan Abu Sittah; Shadi Saleh (Conflict and Health)
Abstract Background Prolonged conflicts in the Middle East and North Africa (MENA) have led to widespread war-related injuries and strained healthcare systems. The absence of standardized trauma registries impedes effective injury assessment, quality of care evaluation, and optimal trauma response. This study explores the challenges associated with trauma data collection, management, and sharing in conflict settings. Methods A qualitative study was conducted via semi structured interviews with 11 experts in trauma care and health data management. The data were collected in English or Arabic, transcribed, and analysed thematically to identify key barriers and potential solutions. Results Four major themes emerged: (1) complexities in data collection (2), challenges in data management and sharing (3), resource and infrastructure limitations, and (4) recommendations for optimizing trauma data. The primary issues identified include the lack of standardized trauma definitions, fragmented data, geopolitical barriers, and inadequate funding. The participants highlighted the need for a minimum consensus-based trauma dataset, local ownership of data, increased financial support, and better integration of trauma data collection into medical education. Conclusion Strengthening trauma data systems in the MENA region will require coordinated efforts focused on standardization, interoperability, and long-term investment in local capacity and infrastructure. Such improvements are critical to supporting evidence-based care and effective response in conflict-affected settings.